2018
DOI: 10.1055/s-0037-1610248
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,3-Diols by O-Nucleophile Additions to Activated Alkenes

Abstract: The diastereoselective synthesis of 1,3-diols by addition of oxygen nucleophiles to activated alkenes is presented. This review focuses on homoallylic alcohol substrates that react with a relay compound to form an intermediate oxygen nucleophile, which in turn will lead to a protected 1,3-diol by intramolecular addition to the olefin moiety.1 Introduction2 Base Catalysis3 Organocatalysis4 Activation with Non-Metallic Electrophiles5 Activation with Transition Metal Derivatives6 Conclusions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…[ 2 , 3 ]. If intramolecular Michael additions are performed with sub-stoichiometric or catalytic bases in a homogenous medium [ 4 ], the bases are rarely recyclable [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 , 3 ]. If intramolecular Michael additions are performed with sub-stoichiometric or catalytic bases in a homogenous medium [ 4 ], the bases are rarely recyclable [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations into the use of cationic Au­(I) complexes in our tandem reaction are currently underway. Importantly, these results demonstrated that, in contrast to previous relevant reactions, our tandem reaction should be applicable to fragment assembly processes in complex polyol synthesis.…”
mentioning
confidence: 82%
“…There has been a longstanding interest in developing efficient methods for stereocontrolled synthesis of 1,3-diol motifs because they are embedded in a plethora of biologically relevant polyketide natural products and pharmaceuticals. , Allylation and aldol reactions of carbonyl compounds are established synthetic methods for accessing 1,3-diol motifs within complex polyketides . Meanwhile, David A. Evans and Gauchet-Prunet have described that hemiacetalization/intramolecular oxa-Michael addition of δ-hydroxy α,β-unsaturated esters/amides with benzaldehyde in the presence of a catalytic amount of a strong base provides syn -1,3-dioxanes, which correspond to benzylidene acetal protected 1,3-diols . This reaction has been widely used in complex polyketide synthesis because of the synthetic versatility of the product syn -1,3-dioxanes .…”
mentioning
confidence: 99%
“…Carbonic acid esters play a critical role in numerous scientific disciplines such as material sciences (e.g., polycarbonates), [1] natural product research (Scheme 1A), [2] and synthetic methodology (Scheme 1B–D) [3] . With regard to the last category, cyclic carbonic acid esters such as 1,3‐dioxolan‐2‐ones and 1,3‐dioxan‐2‐ones have increasingly become a focal point of methodological efforts, since such motifs are frequently shown to serve as lynchpins for the stereoselective synthesis of 1,2‐ [4,5] and 1,3‐diols [6,7] . From a synthetic viewpoint, the olefinic double bond has emerged as a tactically privileged functional group for the construction of cyclic carbonic acid esters by – in part, stereocontrolled – intramolecular cyclizations of carbonate nucleophiles onto inherently or catalytically activated C−C π‐bonds [3,5] .…”
Section: Introductionmentioning
confidence: 99%